2014
DOI: 10.2478/s13380-014-0229-3
|View full text |Cite
|
Sign up to set email alerts
|

Posterior parietal cortex and visuospatial control in near and far space

Abstract: Neuropsychological studies of patients with visuospatial neglect have shown differences in perceptual deficits for information in near space (i.e. near to the body) and information in far space. It has been suggested that among the many areas of the human brain, a number of areas are associated with a set of spatial maps specialized for visuospatial control related to this spatial distinction. This paper reviews how parietal cortex is thought to be involved in visuospatial neglect in relation to its control of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…The same distortion is not present above the knee because in this body zone the audio feedback of movements isn’t present and multisensory integration is similar to the upper body part where the sensory-motor training with ABBI is useful for spatial recalibration (Finocchietti et al, 2017 ). As regard the spatial areas considered, several studies indicate that space is processed differently depending both: the body part considered (Serino et al, 2015 ; di Pellegrino and Làdavas, 2015 ) and on the distance from the body (Làdavas and Farnè, 2004 ; Aimola et al, 2012 ; Tomasino et al, 2012 ; Caçola et al, 2013 ; Mahayana et al, 2014 ). Other studies have found a difference between frontal and rear space (Kóbor et al, 2006 ; Occelli et al, 2011 ; Van der Stoep et al, 2015 ), showing a higher saliency of sounds in the back (Farnè and Làdavas, 2002 ).…”
Section: Discussionmentioning
confidence: 99%
“…The same distortion is not present above the knee because in this body zone the audio feedback of movements isn’t present and multisensory integration is similar to the upper body part where the sensory-motor training with ABBI is useful for spatial recalibration (Finocchietti et al, 2017 ). As regard the spatial areas considered, several studies indicate that space is processed differently depending both: the body part considered (Serino et al, 2015 ; di Pellegrino and Làdavas, 2015 ) and on the distance from the body (Làdavas and Farnè, 2004 ; Aimola et al, 2012 ; Tomasino et al, 2012 ; Caçola et al, 2013 ; Mahayana et al, 2014 ). Other studies have found a difference between frontal and rear space (Kóbor et al, 2006 ; Occelli et al, 2011 ; Van der Stoep et al, 2015 ), showing a higher saliency of sounds in the back (Farnè and Làdavas, 2002 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies suggest that automatic corrections of hand pointings are mainly mediated by the dorsal visual pathway and associated with posterior parietal cortex (PPC) [11,12,13]. The neurological evidence supporting this view comes from the study on bilateral lesion of the PPC [9,14,15], and transcranial magnetic stimulation (TMS) applied to the cortical areas to disrupt the unconscious correction [16]. In addition, the direct evidence of automatic correction in stereoscopic depth has been reported in our recent work [13].…”
Section: Introductionmentioning
confidence: 60%